The Perception of Actors Toward Collaboration in Public Services: Evidence from Civil Registration Services Innovation in the Pangkajene and Island Regency - Rahmayanti, Krisna Puji (UI Scholars Hub, 2021)
This paper aims to analyze the perception of involved actors toward collaboration and investigate conditions that motivate actors to collaborate in delivering public services. This study uses pragmatic philosophy that utilizes qualitative data collection. Despite the government as the leading service provider, non-state actors' involved in planning, organizing, and evaluating service delivery. By conducting a focus group discussion, providing an open question survey, and analyzing relevant news, this research emphasizes that public service providers and communities involved in public service delivery perceived collaboration as working with others or cooperating and achieving common goals. The actors’ belief that achieving common goals is the driver to collaboration. The result also found that developing policies and legal framework to strengthen collaboration is essential to sustain the collaboration.